2022
DOI: 10.3390/cells11243986
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA 148400 Promotes the Apoptosis of Renal Tubular Epithelial Cells in Ischemic AKI by Targeting the miR−10b−3p/GRK4 Axis

Abstract: Although recent studies have reported that long non-coding RNA (lncRNA) is involved in the development of ischemic acute kidney injury (AKI), the exact function and regulatory mechanism of lncRNAs in ischemic AKI remain largely unknown. Herein, we found that ischemic injury promoted the expression of lncRNA 148400 in mouse proximal tubule-derived cell line (BUMPT) and C57BL/6J mice. Furthermore, the lncRNA148400 mediates ischemic injury-induced apoptosis of BUMPT cells. Mechanistically, lncRNA 148400 sponged m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Previous reports showed that lncRNAs could contribute to the development of ischemic AKI [16]. Some lncRNAs protected against the progression of ischemic AKI [16][17][18][19][20][21][22][23][24][25], while others mediated the development of ischemic AKI [4,[26][27][28][29][30][31]. Here, we discovered that mmu-lncRNA 129814/hsa-lncRNA582795 not only mediated I/R-stimulated BUMPT and HK-2 cell death, respectively, but also aggravated the progression of ischemic AKI mice (Figures 2, 3, S2,S4,S5).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous reports showed that lncRNAs could contribute to the development of ischemic AKI [16]. Some lncRNAs protected against the progression of ischemic AKI [16][17][18][19][20][21][22][23][24][25], while others mediated the development of ischemic AKI [4,[26][27][28][29][30][31]. Here, we discovered that mmu-lncRNA 129814/hsa-lncRNA582795 not only mediated I/R-stimulated BUMPT and HK-2 cell death, respectively, but also aggravated the progression of ischemic AKI mice (Figures 2, 3, S2,S4,S5).…”
Section: Discussionmentioning
confidence: 59%
“…It has been recently found that long non-coding RNAs (lncRNAs), > 200 nucleotides, were involved in the progression of ischemic AKI [16]. Some LncRNAs including SNHG14, eosinophil granule ontogeny transcript (EGOT), X-inactive specific transcript (XIST), GAS5,00520, MEG3, mmu-lncRNA 121686/hsa-lncRNA 520657, lncRNA 148400, and lncRNA147219 promoted the development of ischemic AKI [16][17][18][19][20][21][22][23][24][25]. Other lncRNAs including lncRNA 00052, H19, TUG1, 00963, lncRNA 171502, lncRNA 122049, and lncRNA 136131 could alleviate cell apoptosis during ischemic AKI [4,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%